IMPROVING ADAPTIVE COMPETENCE FOR VOCATIONAL EDUCATION TEACHERS IN THE CURRENT CONTEXT - Huong, Truong Thu (IJRDO- Journal of Educational Research, 2019)
Adaptive competence plays an important role in professional activity, helps a person change his/her psychophysiological characteristics, personality to fit, meet the requirement of the activity, to achieve work efficiency and to emprove labor productivity. The Industrial Revolution 4.0 makes many fields change, especially in the education field. In the context, vocational education teachers - one of elements desides the quality of vocational training - must be faced big changes of professional education, such as the change of educational policy, objective, content; needs, competence and learning culture of learners; environment, means, teaching technology... The paper will discuss about the challenges posed to vocational education teachers and some solutions to improve adaptive competence of them, and contribute to improving of the quality of vocational training in the current context.